UTERINE AND OVARIAN SARCOMAS: CLINICAL AND HISTOPATHOLOGICAL CHARACTERISTICS - Tihomir Totev; Desislava Kiprova; Nadezhda Hinkova (Peytchinski Publishing, 2019)
Purpose: To investigate the clinical and histopathological characteristics of patients with uterine and ovarian sarcomas and analyse surgical operations already performed. Material and Methods: The retrospective study included 17 patients with uterine and 2 patients with ovarian sarcomas, who were diagnosed and operated on for three years at St. Marina University Hospital in Pleven, Bulgaria. Results: In the group of uterine sarcomas, the highest incidence was that of leiomyosarcomas (53.3%), followed by endometrial stromal sarcomas (33.3%) and the homologous carcinosarcomas (13.3%). Most of the patients were diagnosed in the first clinical stage (73.3%), and the most common surgery performed was total abdominal hysterectomy with salpingo-oophorectomy, with or without omentectomy (53.3%). The two patients with ovarian tumours were histologically diagnosed with carcinosarcoma. Conclusions: Genital sarcomas are a heterogeneous group of rare malignant diseases with poor prognoses. Early detection, adequate histological diagnosis and staging are of utmost importance for control.